CURRICULAR ENVIRONMENTALIZATION IN PEDAGOGY COURSES AT HIGHER EDUCATION INSTITUTIONS IN THE STATE OF GOIÁS: CHALLENGES AND PROPOSALS (CIPEEX, 2022)
THE MAIN THEME REFERS TO THE ANALYSIS OF CURRICULAR ENVIRONMENTALIZATION ASSOCIATEDWITH ENVIRONMENTAL EDUCATION STUDIES AS A SITUATION ANALYSIS. TEACHERS€™ TRAINING IN BRAZIL,ESPECIALLY IN THE PEDAGOGY COURSE, FOR AT LEAST TWO DECADES, HAS BEEN SEEKING TO OVERCOMEHISTORICAL AND THEORETICAL DILEMMAS OF ITS CURRICULUM DUE TO THE NEW TRAINING DEMANDS OF ITSUNDERGRADUATES. SOME PARTS OF THE SOCIETY STRONGLY TEND TO ATTRIBUTE TO FORMAL EDUCATION, ANDESPECIALLY TO EDUCATORS, THE RESPONSIBILITY TO BEGIN THE PROCESSES OF DESIRABLE CHANGES, BYTEACHING NEW GENERATIONS MORE POSITIVE ATTITUDES TOWARDS SOCIAL ENVIRONMENTAL ISSUES. THEANALYSIS OF PEDAGOGICAL PROJECTS, RELATED TO COORDINATORS€™ AND PROFESSORS€™ SPEECH AND PRACTICEOF PEDAGOGY COURSES, BECOMES RELEVANT SINCE IT WILL CHARACTERIZE THE PROFILE AND CURRENTCONDITIONS OF TEACHERS€™ TRAINING WHO WILL WORK IN EARLY CHILDHOOD EDUCATION. THE CHALLENGES ANDPROPOSALS TOWARDS THE INCLUSION OF THE ENVIRONMENTAL THEME IN THE INITIAL TEACHERS€™ TRAINING,HIGHLIGHTING THE CURRICULAR ENVIRONMENTALIZATION MOVEMENT, IS STILL A CHALLENGE, SINCE IT COMPRISESTHE INCLUSION OF KNOWLEDGE, CRITERIA, SOCIAL, ETHICAL, AESTHETIC AND ENVIRONMENTAL VALUES INCOLLEGE CURRICULUM. IN ORDER TO KNOW WHAT HAS ALREADY BEEN PRODUCED ON THE INCLUSION OFENVIRONMENTAL EDUCATION IN THE BEGINNING OF EDUCATORS TRAINING, A SURVEY OF PUBLISHED STUDIESWAS CARRIED OUT, WITH A QUERY TO THE DATABASE OF THE DIGITAL LIBRARY OF THESES AND DISSERTATIONS(BDTD) OF THE CENTER FOR IMPROVEMENT AND RESEARCH OF HIGHER EDUCATION - CAPES. IN THISSURVEY, THE DISSERTATIONS AND THESES DEFENDED FROM 2015 TO 2022 WERE CONSIDERED. THEENVIRONMENTAL THEME IN THE PEDAGOGY COURSE WOULD BE MORE APPROPRIATE WHEN INSERTED IN ADISCIPLINARY OR INTERDISCIPLINARY WAY AND IT WAS VERIFIED THAT, ALTHOUGH THERE IS A CONSENSUS AMONGTHE SUBJECTS REGARDING THE NEED FOR ITS INCLUSION, THERE ARE, ON THE OTHER HAND, DISAGREEMENTSREGARDING THE €ŒOPERATIONALIZATION€ OF IT. THERE ARE ALSO LIMITATIONS IMPOSED ON ENVIRONMENTALEDUCATION IN THE CURRICULUM, SUCH AS: TEACHER TRAINING, SPECIFICITIES OF THE DISCIPLINES,FRAGMENTATION OF SPACE/TIME, AND CONTRADICTIONS RELATED TO THE SYSTEM. THE NEED FOR RESEARCH ONTHIS PEDAGOGY-ENVIRONMENTAL EDUCATION RELATIONSHIP FOR THE STATE OF GOIS IS CONCLUDED, SINCETHE INTERDISCIPLINARY APPROACH TO THE CURRICULUM IS ADDED TO THE STILL TRADITIONAL SPEECH WITH FEWENVIRONMENTAL PROJECTIONS.
Keywords: currículo; Goiás; ecopedagogia